Genomic Analysis of a Novel Antarctic Bacterium, Cryobacterium sp. SO2 Provides Insights into its Genomic Potential for Production of Antimicrobial Compounds - Teoh, Chui Peng; Lavin, P.; González-aravena, M.; Clemente Michael Wong Vui Ling (Universiti Kebangsaan Malaysia, 2023)
A novel strain of Cryobacterium designated as SO2, was isolated from the Antarctic. Hence, this study was undertaken to gain further insight into the antimicrobial compounds and secondary metabolites produced by Cryobacterium sp. SO2. It was found that strain SO2 is a Gram-positive that exhibits an irregular rod shape, which formed yellow to orange pigmented colonies on semi-solid media. Strain SO2 grows at temperatures ranging from 4 to 25 ºC. It has a complete genomic size of 4.097 Mb. SO2 has a DNA G+C content of 68.43%, and genomic annotation showed that the genome contained 3,862 CDS, 10 rRNA, 55 tRNA and 1 tm-RNA. Phylogenetic and OrthoANI analysis suggested Cryobacterium sp. strains SO1, N22, TMB1-8, LW097, TMN39-1, C. zongtaii TMN-42, C. arcticum PAMC27867 and C. soli GCJ02 as its closest phylogenetic neighbour. Genome annotation shows that strain SO2 confers β-lactamase class A, cephalosporin-C deacetylases, and 27 drug-resistance or efflux coding genes, and allows resistance to ceftazidime. Functional annotation identifies 28.74% of predicted genes are of unknown functions. Genome mining indicates that there are six putative secondary metabolite gene clusters in strain SO2. They are made up of RRE-containing, terpene, beta-lactone, T3PKS, NAPAA, and 2dos. This finding shows strain SO2 harbours genes that may be involved in the production of compounds with antibacterial and antioxidant activities.